1990
DOI: 10.1366/0003702904085499
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon Solute Probes. Part VI: Effect of Dissolved Oxygen and Halogenated Solvents on the Emission Spectra of Select Probe Molecules

Abstract: Fluorescence emission properties of pyrene, benzo[ ghi]perylene, coronene, and ovalene dissolved in carbon tetrachloride, chloroform, and dichloromethane are reported. Measurements indicate that the emission intensities of select solutes are time dependent, and suggest that the polycyclic aromatic hydrocarbon molecule undergoes a photochemical reaction with the chlorinated solvent. The effect of dissolved oxygen on the experimental ratio of emission intensities is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The emission peak of these dyes shifted to longer wavelength on increasing the solvent polarity. [44] An abnormal red-shifted emission was observed in CHCl 3 for all of these compounds, which may be attributed to the involvement of carbene species that are generated upon the photoexcitation of [45] Notably, the electron-rich nature of the molecule dictated the outcome of such photochemical reactions. [43] The blue-shifted emission in MeOH may be ascribed to hydrogen-bonding interactions, which probably retard the reorientation of the fluorophore in the excited state by hindering the rotation of the aryl unit ( Figure 5).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…The emission peak of these dyes shifted to longer wavelength on increasing the solvent polarity. [44] An abnormal red-shifted emission was observed in CHCl 3 for all of these compounds, which may be attributed to the involvement of carbene species that are generated upon the photoexcitation of [45] Notably, the electron-rich nature of the molecule dictated the outcome of such photochemical reactions. [43] The blue-shifted emission in MeOH may be ascribed to hydrogen-bonding interactions, which probably retard the reorientation of the fluorophore in the excited state by hindering the rotation of the aryl unit ( Figure 5).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…A systematic experimental investigation on a series of polycyclic aromatic hydrocarbons (PAHs) [8,9,10,11,12,13,14,15,16,17,18] for a variation in selective vibronic bands with respect to solvent polarity show that the PAHs broadly fall in to three categories. The first category of PAHs include pyrene, benzo[ghi]perylene, etc which exhibit a selective emission intensity enhancement of vibronic band I relative to band III (I/III) in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In water, it has been suggested that the first step involves an electron transfer from the excited singlet state of pyrene to molecular oxygen in a contact charge-transfer pair, followed by the reaction of the pyrene radical cation with water, leading to 1-hydroxypyrene as the initial photoproduct. A similar mechanism has been suggested for the photodegradation of pyrene on silica surfaces in the presence of oxygen (under simulated laboratory irradiation conditions and solar irradiation), where 1-hydroxypyrene is generated through the reaction of the pyrene radical cation with physisorbed water.…”
Section: à3mentioning
confidence: 99%
“…In spite of that, the pyrene chromophore is still used in chloroform for applications related to its fluorescent properties, because of its good solubility properties. [12] Interestingly, even though pyrene quickly transforms into stable photoproducts (whose structures have not been studied) when irradiated (l exc = 338 nm) in CCl 4 , [13] its photodegradation quantum yield in dichloromethane [14] (l exc = 311 nm, high-pressure lamp in combination with an interference filter) is similar to that in water [15] (1.8 10 À3 vs 2.1 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation